Analysis Of Quarry Material Characteristics In Reclamation Work Using Sand Cone And CBR Methods (Case Study: Patimban Port Package 5) - Alvin Alfahreza; Aldi Firmansya; Sultan Arya Faza; Arief Firmanto (Riviera Publishing, 2025)
Soil compaction is an important process in reclamation work because it has a direct effect on the carrying capacity and stability of the structure built on it. This study was conducted in one of the specific work zones of Area C1a in the Patimban Port reclamation project, where sand material from various quarry sources is used, each having different physical characteristics that can affect the success of compaction. This study aims to analyze and compare the results of material compaction from four different quarries using the field density test (sand cone) and laboratory carrying capacity test (CBR) methods. The research methodology includes the analysis of physical characteristics such as particle size distribution and sludge content, as well as compaction quality testing after applying the same number of vibratory roller passes to each material. The results showed that the material from Quarry A achieved the highest average field density (104.71%), indicating the highest compaction effectiveness among the materials tested. In terms of carrying capacity, the material from Quarry B proved to be the most superior, with the highest CBR value both in dry conditions (103.00%), after submersion (58.00%). In contrast, the Quarry C material showed the highest sensitivity to water, as its CBR value decreased from 75.00% to 27.00% when submerged, which correlated with the highest silt content (9.21%). These findings demonstrate that the physical characteristics of materials, such as silt content and grain size distribution, are the main determining factors affecting the final yield of soil density and carrying capacity.